2004
DOI: 10.1016/s0020-7292(03)00342-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of insulin, IGF‐1, and IGFBP‐1 in pre‐eclampsia and eclampsia

Abstract: IGF-1 was lower, and IGFBP-1 was higher in pre-eclamptic and eclamptic patients than controls, these alterations were related to the severity of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Progesterone levels are reported to be increased in preclamptic pregnancies [28,29], which are associated with a reduction in subsequent BC, particularly in older primiparas and in the first few years following delivery [12] (Table 1). However, relative to normal pregnancies, those complicated by preclampsia are also typified by decreased levels of estrogens [28,30] and IGF-I [28,31,32], and by elevated levels of androgens [28,30,33,34], IGF binding protein-1 [28,31], hCG [28,[35][36][37] and AFP [37,38] (Table 4). All these factors may act both individually and synergistically to decrease BC risk by reducing proliferative growth of mammary tissue and by inhibiting the malignant transformation of precancerous lesions or the promotion of occult neoplasms [12].…”
Section: Hormonal Factors That Affect Breast Tissue Modifications Andmentioning
confidence: 99%
“…Progesterone levels are reported to be increased in preclamptic pregnancies [28,29], which are associated with a reduction in subsequent BC, particularly in older primiparas and in the first few years following delivery [12] (Table 1). However, relative to normal pregnancies, those complicated by preclampsia are also typified by decreased levels of estrogens [28,30] and IGF-I [28,31,32], and by elevated levels of androgens [28,30,33,34], IGF binding protein-1 [28,31], hCG [28,[35][36][37] and AFP [37,38] (Table 4). All these factors may act both individually and synergistically to decrease BC risk by reducing proliferative growth of mammary tissue and by inhibiting the malignant transformation of precancerous lesions or the promotion of occult neoplasms [12].…”
Section: Hormonal Factors That Affect Breast Tissue Modifications Andmentioning
confidence: 99%
“…On the other hand, it has been found that preeclampsia is associated with decreased circulating levels of insulinlike growth factor I (IGF-I) [10][11][12][13][14][15]. Interestingly, IGF-I is considered as a regulator of 1,25-(OH) 2 D synthesis, since it stimulates renal [16,17] and placental [18] calcitriol production.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies report low IGF-I levels in women who go on to develop preeclampsia (42,43) and those with established disease (44). In light of the findings of the current study, it is possible that this double insult may contribute to the abnormal blood flow associated with this condition.…”
Section: Discussionmentioning
confidence: 54%